2021
DOI: 10.1177/00472875211030328
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Tourists’ Site-Specific Environmentally Responsible Behavior: An Eco-Sensitive Zone Perspective

Abstract: This study examines the role of individual values, attitudes, and situational reasons for determining site-specific environmentally responsible behavior (s-ERB) at eco-sensitive zones. It deploys a mixed-methods approach that includes in-depth interviews with 25 visitors to elicit reasons for/against s-ERB, and a survey of 540 visitors to empirically validate the proposed model using structural equation modeling. The qualitative interviews evoked four reasons for s-ERB (felt responsibility, environmental knowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 167 publications
(344 reference statements)
3
28
0
Order By: Relevance
“…Third, for the embedded situations, the national park situation and the social environmental culture atmosphere all had positive moderating effects on ERB. The research of Gupta et al (2021) showed that the site-specific environment affects the ERB of visitors [6], and this study once again confirmed that when visitors are in the site-specific environment of Shennongjia National Park, this environment has a positive impact on visitor ERB. The national park situation is formed by environmental protection activities, facilities, interpretation system and staff guidance.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Third, for the embedded situations, the national park situation and the social environmental culture atmosphere all had positive moderating effects on ERB. The research of Gupta et al (2021) showed that the site-specific environment affects the ERB of visitors [6], and this study once again confirmed that when visitors are in the site-specific environment of Shennongjia National Park, this environment has a positive impact on visitor ERB. The national park situation is formed by environmental protection activities, facilities, interpretation system and staff guidance.…”
Section: Discussionsupporting
confidence: 71%
“…How to convince protected area visitors to practice greater ERB? There are many studies on how to promote the ERB of visitors to nature reserves [6][7][8]. This research explored influential factors to provide a scientific basis for building a stronger environmental protection culture and increased ecological protection awareness.…”
Section: Introductionmentioning
confidence: 99%
“…Environmentally responsible behavior comprises the actions that individuals purposely take to reduce adverse impacts on a specific destination (Lee et al 2013; Steg and Vlek 2009). Because of the potential benefits of tourists’ ERB to the destination, much research has been conducted on its antecedents, such as demographic and subjective norms (e.g., Han et al 2017; Lee and Jan 2015), destination perception and relationship quality (e.g., He et al 2018; Lin et al 2019), involvement and recreation experience (e.g., Lee and Jan 2015; Lin and Lee 2020), knowledge and attitudes (e.g., Gupta et al 2021; Holmes et al 2021; Passafaro 2020), subjective well-being and satisfaction (e.g., Chiu et al 2014; Su et al 2018), emotional and place attachment (e.g., Su and Swanson 2017), ascribed responsibility (e.g., Confente and Scarpi 2021; Han et al 2018), and social responsibility (e.g., Su and Swanson 2017; Su et al 2020). However, most of these studies have focused on the factors influencing tourists’ ERB at the individual or destination levels and have not considered the effect of the interactions between residents and tourists.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…The individual willingness to initiate and implement the CSR policies highly depends on their attitude toward protecting the earth's heritage. Given the articulation, the research shows that increasing environmental concerns have made the employees develop a positive attitude toward environment protection activities (Gupta et al, 2021). In particular, the employees' attitudes and perceptions provide a recreational opportunity, improving the environmental welfare.…”
Section: Attitude Toward Environmental Corporate Social Responsibilit...mentioning
confidence: 99%